Penerapan Lean Manufacturing untuk Pengaplikasian Price Term Terbaik melalui Analisis TOPSIS: Kasus Industri Elektronik Berfasilitas Kawasan Berikat - Mochamad Eko Nugroho (Universitas Mercu Buana, 2022)
To maintain customer loyalty, punctual delivery is needed. In Indonesia, the government has regulated industrial regulations, especially manufacturing with imported raw materials through the provision of special facilities. One of these facilities is a bonded zone facility. In the application to the procurement process, several special rules extend the flow of the goods procurement process which is feared to have an impact on delivery delays and large inventory levels. In terms of price term performance, the TOPSIS method is used, and the data is taken from questionnaires the Korea CKD Import Planner, China CKD Import Planner, Chemical Import Planner, and Steel Sheet Import Planner, with criteria for late delivery of goods, incomplete document completeness, length of COO processing. Certificate of Origin), duration of export-import licensing, risk in shipping, selection of forwarder (3PL), selection of vessel schedule, and costs. From the results of the questionnaire, a normalized matrix was made. From this matrix, the distance between positive and negative solutions is sought so that the preference value of each alternative is obtained, and the price term CIP (Cost & Insurance Paid) is obtained as the price term with the closest relative closeness with a value of 0.5042.